The Influence of the Character-Oriented Rambu Solo’ Ceremony-Based Learning Model (Purso) on Improving Learning Outcomes in Civics Education - Allolinggi, Lutma Ranta; Maminiaina (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to investigate the effect of the Character-Oriented Rambu Solo’ Ceremony-Based Learning Model (PURSO) on students’ learning outcomes in Civics Education. The integration of local cultural values into character education is considered essential to fostering moral, social, and cognitive development among elementary school students. Method:This study adopts a quasi-experimental design using a "true experimental design" with a post-test-only control group. The population consisted of 28 students at an elementary school in Toraja Regency during the 2024/2025 academic year. Using simple random sampling, two groups were selected: an experimental group taught using the PURSO model and a control group taught through conventional methods. Data collection was conducted using post-tests and questionnaires. Statistical analysis included normality and homogeneity tests, independent sample t-tests, and mastery learning tests. Results: The findings of this study revealed a significant difference in learning outcomes between the experimental and control groups. Students who received instruction through the PURSO character-oriented learning model achieved higher post-test scores. In the experimental group, 25 out of 28 students (89.29%) met the Minimum Completeness Criteria (MCC), whereas only 18 out of 28 students (64.29%) in the control group achieved the same standard. The independent samples t-test yielded a t-value of 4.32 with a significance level of p = 0.000 (p < 0.05). These results indicate that the implementation of the PURSO learning model has a significant and positive impact on improving students' learning outcomes in Civics Education. Novelty: This research introduces a novel learning model by incorporating the cultural values of the Rambu Solo’ funeral ceremony into formal Civics Education. Unlike conventional models, PURSO enhances not only academic achievement but also character formation, making learning more contextual and culturally responsive